1978
DOI: 10.3758/bf03214296
|View full text |Cite
|
Sign up to set email alerts
|

Constancy of egocentric visual direction

Abstract: Two experiments investigating the constancy of egocentric visual direction were conducted. In Experiment 1, subjects indicated when a briefly exposed light was subjectively straight ahead during various degrees of asymmetric convergence. The results indicated that the perception of direction exhibited systematic underconstancy. The departures from constancy were dependent upon the degree of asymmetric convergence, increasing as asymmetric convergence increased. Experiment 2 investigated the source of undercons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(35 citation statements)
references
References 14 publications
6
29
0
Order By: Relevance
“…Several researchers have shown that people are able to point accurately to the location they are fixating, even in complete darkness (Hill, 1972;Morgan, 1978). If fixation location in the earlier experiments was somehow affected by the response condition, then differences that we observed in the pointing responses may have been mediated by differences in eye position.…”
Section: Resultsmentioning
confidence: 48%
See 2 more Smart Citations
“…Several researchers have shown that people are able to point accurately to the location they are fixating, even in complete darkness (Hill, 1972;Morgan, 1978). If fixation location in the earlier experiments was somehow affected by the response condition, then differences that we observed in the pointing responses may have been mediated by differences in eye position.…”
Section: Resultsmentioning
confidence: 48%
“…Some researchers have chosen to explore the former issue, whereas others have focused on the latter. For example, a number of researchers have examined localization as a function of the number and type of eye movements that subjects use to fixate a target to be localized (Festinger & Canon, 1965;Honda, 1984Honda, , 1985, or as a function of the retinal location of the target (Hill, 1972;Morgan, 1978). These studies have mainly been concerned with potential differences in the information available about a visual target after different types of stimulation.…”
Section: Differential Use Of Distance and Location Information For Spmentioning
confidence: 99%
See 1 more Smart Citation
“…Morgan (1978) reported errors in egocentric direction attributable to misrepresentation in eye position. The amount of error depended on the amount of rotation of the eye from the primary direction of gaze; greater rotation led to greater error in directionalization and, by implication, to greater misrepresentation of eye position.…”
Section: Between-eye Differences In Slope: Non-central Cyclopean Eye?mentioning
confidence: 99%
“…This may explain the tendency of subjects to underestimate the amount of rotation of their own eyes away from the straight-ahead position. This tendency was studied quantitatively by Morgan (1978), who had subjects fixate an eccentric target and then estimate whether another target was left or right of center (azimuth) in an otherwise unstructured field. There was a linear relationship between eccentricity of the fixation target and error in judging the straight-ahead direction.…”
Section: Remainder Effectmentioning
confidence: 99%